Assessment of amyloglucosidase activity during production and storage of laminated pie dough. Impact on raw dough properties and sweetness after baking. (January 2015) - Diler, Guénaëlle; Chevallier, Sylvie; Pöhlmann, Inga; Guyon, Claire; Guilloux, Marion; Le-Bail, Alain
Abstract: Amyloglucosidase (AMG) is an enzyme that hydrolyzes starch into glucose units. AMG activity was tested in a model pie dough during the dough-making process (after mixing and sheeting) and during storage for 4 weeks at 4 °C. The activity was quantified by measuring the glucose content of dough and baked products using HPLC. The consequences of AMG activity on the sweet taste of the baked products (sensory ranking test) and on the rheological properties of the dough were studied and compared with a control dough formulated with sucrose. The results showed a significant production of glucose during the dough-making process and during baking when AMG was used. During the dough-making process, AMG activity was limited by the substrate. During baking, the substrate was no longer a limiting factor and the amount of glucose released was directly proportional to the amount of AMG used. The mixing time was increased and the elastic properties of the dough decreased when AMG was added. However, these impacts of AMG on dough properties were not as significant as those of sucrose addition. Addition of 0.75% AMG (flour basis) developed a sweet taste equivalent to that obtained by addition of 17% sucrose (flour basis). Highlights: Glucose is produced during the main steps of the dough-making process in the presence of AMG. The glucose released in the dough is independent of the quantity of AMG added. Sugars released by AMG activity lead to a decline in the elastic properties of the dough. Using 0.75% AMG yields a sweet taste comparable to that obtained with 17% sucrose (% on flour basis).